Bridging the Gap Between Prosody and Pragmatics: The Acquisition of Pragmatic Prosody in the Preschool Years and Its Relation With Theory of Mind - Pronina, Mariia; Hübscher, Iris; Vilà-Giménez, Ingrid; Prieto, Pilar (Frontiers in Psychology, 2021)
While it is well known that prosodic features are central in the conveyance of pragmatic meaning across languages, developmental research has assessed a narrow set of pragmatic functions of prosody. Research on prosodic development has focused on early infancy, with the subsequent preschool ages and beyond having received less attention. This study sets out to explore how young preschoolers develop the ability to use prosody to express pragmatic meanings while taking into account children’s Theory of Mind (ToM) development. Though ToM has been suggested to be linked to the development of receptive prosody, little is known about its relationship with expressive prosodic skills. A total of 102 3- to 4-year-old Catalan-speaking children were assessed for their pragmatic prosody skills using 35 picture-supported prompts revolving around a variety of social scenarios, as well as for their ToM skills. The responses were analyzed for prosodic appropriateness. The analyses revealed that 3- to 4-year-olds successfully produced prosody to encode basic expressive acts and unbiased speech acts such as information-seeking questions. Yet they had more trouble with complex expressive acts and biased speech acts such as the ones that convey speakers’ beliefs. Further analyses showed that ToM alone is not sufficient to explain children’s prosodic score, but the prosodic performance in some pragmatic areas (unbiased pragmatic meanings) was predicted by the interaction between ToM and age. Overall, this evidence for the acquisition of pragmatic prosody by young preschoolers demonstrates the importance of bridging the gap between prosody and pragmatics when accounting for prosodic developmental profiles, as well as taking into account the potential influence of ToM and other socio-cognitive and language skills in this development.